Chlorine dioxide as a disinfectant for Ralstonia solanacearum control in water, storage and equipment - Popović Tatjana; Ivanovic Žarko; Janjatović Sanja; Ignjatov Maja; Milovanović Predrag (Ratarstvo i Povrtarstvo, 2016)
Brown rot or bacterial wilt caused by bacterium Ralstonia solanacearum is the main limiting factor in potato production. Quarantine measures are necessary to avoid spread of disease to disease-free areas. R. solanacearum has been shown to contaminate watercourses from which crop irrigation is then prohibited causing further potential losses in yield and quality. The bacteria also spread via surfaces that diseased seed potatoes come into contact with. This study showed bactericidal activity of chlorine dioxide (CIO2) on R. solanacearum for disinfection of water, surface and equipment. The results showed that CIO2 solution at concentration of 2 ppm at 30 minutes of exposure time had bactericidal effect for disinfection of water. For surface and equipment disinfection, concentration of 50 ppm showed total efficacy at 30 min and 5 sec exposure time, respectively. Results suggest that use of CIO2 as a disinfectant has a potential for control of brown rot pathogen in water, storage and equipment.